(untitled) (Iraqi Journal of Medical Sciences, 2019)
Background:Breast cancer has a major impact on health of women worldwide and Yemen is not in exception. Fingerprints play an important role, which is highly individualistic and could be recognized as a powerful tool in diagnosis of various diseases, furthermore, their medico-legal importance. Objective:To study the clinico-pathological aspects of breast cancer and the role of fingerprints as screening test. Methods:Prospective study of 68 female patients with breast cancer came to modern histopathology laboratory - Aden during the period from January - June 2018. All the patients suffering from breast lumps were referred for Fine Needle Aspiration Cytology diagnosis as well as fingerprints of their both hands were taken. Results:Most of the participants (45.6%) aged between 40-49 years old, females from urban areas consisted 57.4%, and about 51.5% of females in this study were illiterate. Females who had 1-3 child consisted 33.8%. Regarding the breast lump, 54.4% of females had tumor size 2-5 cm, while skin change and fixed tumor to skin presented in same rate (14.8%). No pain and no nipple discharge present in 85.2% and 91.2% respectively in females’ study. The females with palpable axillary lymph nodes and right breast side tumor consisted the same percentage (58.8%). Regarding the result of fine needle aspiration cytology, the invasive ductal carcinoma presented with high rate (85.3%), while stage II present with 36.8%. In relation to the finger print patterns; the loop patterns presented high rate in the little digit with 30.4%, while whorls patterns presented in index digit in 33.6% of patients. The loops and whorls patterns revealed significant association with breast cancer with a P-value of 0.005 and 0.028 respectively. Conclusion:The social, behavioral, and hereditary factors play an important role in the development of breast cancer in addition to reproductive history, beside that the fingerprints are genetically determined factors that can be used as simple and cost-effective screening test for breast cancer. Keywords:Breast carcinoma, fingerprints, Dermatoglyphic, forensic, Yemeni female. Citation:Bin Thabit MA, Abdullah NA, Alnoban MS. Breast Cancer in a sample of Yemeni female patients: forensic dermatoglyphic traits and clinico-pathological features. Iraqi JMS. 2019; 17(2): 135-145. doi: 10.22578/IJMS.17.2.7